Essential Theory for Social Work Practice - Beckett, Chris (SAGE Publications, Ltd. (UK), 2015)
Focusing on what students really need to know, this book breaks down all of the key social work theory covered across a students′ training, demystifying complex concepts by demonstrating their application to real-life practice. Multiple case studies highlight applied theory in different practice settings and across issues and challenges that students might face, while self-assessment exercises, practice notes, concise chapter summaries and discussion points help to consolidate their understanding. New chapters bring the book right up to date and include Relationship-based Work, The Importance of Language, Political Perspectives and Environmental Intervention. Written by two well-established and expert authors, this is the ′must-have′ theory text for all social work students.